HUBUNGAN KEBERSYUKURAN DENGAN TEACHER WELL-BEING PADA GURU YANG MENGAJAR DI SEKOLAH DASAR INKLUSI - Fitri Lestari Issom; Zulfa Nadia (Perspektif Ilmu Pendidikan, 2021)
This research aims to find the relationship between gratitude and teacher well-being for teachers who teach in inclusive elementary schools. The research method used is quantitative with descriptive analysis techniques and correlation analysis. The sample in this study was 185 inclusive elementary school teachers obtained by purposive sampling technique. The gratitude variable was measured using The Gratitude Questionnaire-Six Item Form (GQ-6) developed by McCullough, Emmons, and Tsang (2002) and the teacher well-being variable was measured using the Teacher Well-Being Scale (TWBS) developed by Collie et al. (2015). The results of the correlation analysis show that there is a significant relationship towards positive gratitude with teacher well-being for teachers who teach in inclusive elementary schools. The positive relationship between gratitude and teacher well-being is defined as the higher the gratitude, the higher the teacher well-being of teachers who teach in inclusive elementary schools.